PENGARUH HARGA DAN KUALITAS KUALITAS PELAYANAN TERHADAP MINAT BELI CALON PENUMPANG DI PT. TRI MITRA BATAM - Mursalina, Veby; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2021)
This research was conducted by multiple linear regression analysis methods and hypothesis tests with the aim of knowing the impact between price and quality of service on consumer buying interests. The population in this study is consumers who make purchase transactions at PT.Tri Mitra Batam with the determination of samples using slovin formula. The data collected in this study is from questionnaires that are disseminated through google form and processed using SPSS Version 26 software. Multiple linear regression analysis results show the value of Y = 30,014 + 0.109X1 + 0.303X2 + e. The result of the coefficient of determination (R2) is 0.219. From the result t obtained t value count < t table is 1.76 < 1.98 which shows that the price doesn’t have a positif and significant influence of buying interest. For variable quality of service value t calculate > t table is 4,969 > 1.98 which shows positive and significant results between quality of service to buying interest. F test results show the value of F count > F table is 15,001 > 3.08 so it can be said that the variable price and services simultaneously affects the variable consumer buying interest in PT.Tri Mitra Batam